Myrcia suberosa: a new species of Myrcia sect. Eugeniopsis (Myrciinae, Myrteae, Myrtaceae) endemic to the Atlantic Forest - Santos, Matheus Fortes; Fernandes, Thiago (Phytotaxa, 2020)
A new species, Myrcia suberosa, is here proposed based in an ongoing taxonomic revision of Myrcia sect. Eugeniopsis, a group nearly endemic to the Atlantic Forest. Myrcia suberosa occurs in Brazil from Southern Bahia to Southern Rio de Janeiro states, but only three collections are known and the real distribution of the species is barely known. The new species is morphologically related to Myrcia pseudomarlierea and Myrcia teuscheriana, differing by sexual system, cork thickness, indument, and leaf and flower morphologies. Morphological description, images and conservation status are provided, as well as discussion about distribution, habitat, phenology and taxonomy.